Harnessing indigenous knowledge and practices for effective adaptation in the Sahel - Zougmoré, Robert B.; Segnon, Alcade Christel; Thornton, Philip K. (Elsevier, 2023)
The Sahel region of West Africa has experienced some of the most severe multidecadal rainfall variability over the past 50 years. Based on recollections of the past and observations of the present, local communities in the Sahel have developed extensive knowledge and understanding of their environment and climate that enables them to harness ecosystem services to support their livelihoods and survive environmental changes. Recent literature indicated that farmers’ knowledge and perceptions of changes in the local climate are largely consistent with observed meteorological data, except for the more heterogeneous precipitation change. This understanding of changes in their environment combined with their indigenous knowledge can be particularly useful in data-sparse regions such as the Sahel. This review highlights the importance of indigenous knowledge in enabling effective adaptation in the Sahel and beyond. It outlines some future research avenues for fostering indigenous knowledge-based adaptation, including addressing barriers to mainstreaming of indigenous knowledge into climate research and policy.